2007
DOI: 10.1016/s1472-6483(10)60873-5
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic investigations in couples with repeated miscarriages and malformed children: report of a novel insertion

Abstract: Recurrent miscarriage and the birth of a malformed child continue to be challenging problems for the patient and clinician. Often, cytogenetic studies have an important role in the evaluation of couples with a poor obstetric history. The present study deals with analysis of chromosome abnormalities in 2150 couples from India, and is the largest group ever reported in the literature. The observed incidence of chromosomal rearrangements in these couples was 3.5%. Apart from reciprocal, Robertsonian, inversions, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 21 publications
3
10
3
Order By: Relevance
“…The first couple was reported in India by Rao L et al, who noticed an insertion in women with karyotype 46,XX,ins(12:6)(12;6)(q24.2;q23q25) [41]. The second was reported by Iyer P, who identified an insertion in men with karyotype 46,XY,ins(1;13)(q22;q31q33) [42], and the third was reported by Fuente-Cortés BED, who found an insertion in women with karyotype 46,XX,ins(15;8)(q26;p11p23) [16]. In our study, we identified a new insertion, 46,XX,ins(6)(p24q21q27), in one woman with RSM, and to the best of our knowledge, this is the fourth insertion reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…The first couple was reported in India by Rao L et al, who noticed an insertion in women with karyotype 46,XX,ins(12:6)(12;6)(q24.2;q23q25) [41]. The second was reported by Iyer P, who identified an insertion in men with karyotype 46,XY,ins(1;13)(q22;q31q33) [42], and the third was reported by Fuente-Cortés BED, who found an insertion in women with karyotype 46,XX,ins(15;8)(q26;p11p23) [16]. In our study, we identified a new insertion, 46,XX,ins(6)(p24q21q27), in one woman with RSM, and to the best of our knowledge, this is the fourth insertion reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to Robertsonian and reciprocal translocations and inversions, there are also polymorphic variants on chromosomes that are considered 'normal' by cytogeneticists because they involve heterochromatic regions and occur in the general population without apparent clinical significance [Borgaonkar 1997]. However, previous studies have reported that the incidence of these variants is higher in infertile patients [Madon et al 2005], couples suffering from recurrent miscarriage [Iyer et al 2007], and in men with poor sperm quality [Nakamura et al 2001;Nagvenkar et al 2005;Collodel et al 2006]. These variants are quantitative/positional modifications of constitutive heterochromatin.…”
Section: Introductionmentioning
confidence: 99%
“…Often cytogenetic studies have an important role in the evaluation of couples with a poor obstetric history [1] . Repeated pregnancy loss in first trimester is strongly associated with chromosomal abnormality in couples [2], [3] .…”
Section: Imentioning
confidence: 99%